2017
DOI: 10.1177/0961203317725590
|View full text |Cite
|
Sign up to set email alerts
|

The use of heart rate turbulence and heart rate variability in the assessment of autonomic regulation and circadian rhythm in patients with systemic lupus erythematosus without apparent heart disease

Abstract: Our study confirms the presence of autonomic disorders with respect to both heart rate variability and heart rate turbulence parameters and the presence of diurnal disturbances of sympathetic-parasympathetic balance. Further studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…compared 26 patients with SLE and 30 healthy subjects (age, sex and basic anthropometric parameters-matched) using 24-hour ambulatory ECG monitoring. 26 HRV and HRT analyses were performed for the entire day, and also separately for daytime activity (between 08:00 and 12:00) and night time rest (between 24:00 and 04:00). In the 24-hour analysis, most of the HRV parameters were significantly lower in the SLE patients when compared with the controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…compared 26 patients with SLE and 30 healthy subjects (age, sex and basic anthropometric parameters-matched) using 24-hour ambulatory ECG monitoring. 26 HRV and HRT analyses were performed for the entire day, and also separately for daytime activity (between 08:00 and 12:00) and night time rest (between 24:00 and 04:00). In the 24-hour analysis, most of the HRV parameters were significantly lower in the SLE patients when compared with the controls.…”
Section: Resultsmentioning
confidence: 99%
“…HRV: heart rate variability; NN: normal-to-normal; PNS: parasympathetic nervous system; PVC: premature ventricular contraction; SNS: sympathetic nervous system. 13,19,49 26 HRV and HRT analyses were performed for the entire day, and also separately for daytime activity (between 08:00 and 12:00) and night time rest (between 24:00 and 04:00). In the 24-hour analysis, most of the HRV parameters were significantly lower in the SLE patients when compared with the controls.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the patients with RA and SLE have marked autonomic dysfunction with sympathetic predominance in the patients with SLE and parasympathetic predominance in the patients with RA. Poliwczak et al 23 reported heart rate turbulence and HRV results of their adult patients with SLE without apparent heart disease. Their study confirmed the presence of autonomic disorders with respect to both HRV and heart rate turbulence parameters and the presence of diurnal disturbances of sympathetic-parasympathetic balance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the observed changes in HRV under different conditions are often less than 20% (Buccelletti et al, 2009; Pieters et al, 2012). Given the overlap in HRV values between normal and altered physiological states (Rajendra Acharya et al, 2006; Benichou et al, 2018; Poliwczak et al, 2018), our proposed data exclusion method is likely to be applicable to most physiological/pathological conditions. Furthermore, our results showed that % change exclusion criterion is a feasible way for analyzing long-term recordings, providing a basis for future studies looking at pathological conditions.…”
Section: Discussionmentioning
confidence: 99%